The accuracy of plain radiographs in diagnosing degenerate rotator cuff disease. (May 2019) - Chin, Kuen; Chowdhury, Alex; Leivadiotou, Dimitra; Marmery, Helen; Ahrens, Philip Michael
Background: A number of radiographic signs have been previously demonstrated to be associated with degenerative rotator cuff tears. An ability to predict the presence of a tear by radiography would permit the early commencement of appropriate treatment and the avoidance of unnecessary invasive investigations. The aim of the present study was to determine the accuracy of using radiographic signs to predict the presence of a cuff tear on arthroscopy. Methods: Fifty consecutive patients who had undergone shoulder arthroscopy and had pre-operative plain radiographs were included. Pre-operative radiographs were reviewed by a consultant shoulder surgeon, a consultant radiologist and a senior clinical fellow for the following signs: acromial spur; subjective reduction of subacromial space; sourcil sign; acromial acetabularization; os acromiale; greater tuberosity cortical irregularity; greater tuberosity sclerosis; humeral head rounding; cyst; and reduction in acromiohumeral head distance. Results: The presence of tuberosity sclerosis ( p < 0.0001), tuberosity irregularities ( p < 0.0001), tuberosity cyst ( p = 0.004) and sourcil sign ( p = 0.019) was associated with the presence of a rotator cuff tear. The combined sensitivity of prediction of tear by the observers following radiographic review was 91.7%, with a combined negative predictive value of 80%. Conclusions: The assessment of radiographs by senior clinicians is a useful tool for confirming the absence of a rotator cuff tear.